2019
DOI: 10.5539/ijbm.v14n6p43
|View full text |Cite
|
Sign up to set email alerts
|

Factors Driving the Adoption of E-banking Services Based on the UTAUT Model

Abstract: E-banking has become one of the most popular methods that has experienced considerably great attention in the financial services studies in the last few years. E-banking enables customers of the bank to conduct a range of financial services via the internet portal. It provides a solution in driving formal banking services uptake in the most cost-effective way, it has great benefits to both the customers as well as the banks i.e. convenience, cost reduction, ease and is an effective marketing tool. This researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…For example, in a study on the factors driving the adoption of E-banking services in Zambia based on the UTAUT Model, it was revealed that the UTAUT factors; performance expectancy, effort expectancy, facilitating conditions and behavior intention have a significant impact in the adoption of e-banking services. Social influence was non-significant to the user's intention to adopt e-banking services [12]. Some of the results from these studies are consistent with the original postulations while others contradict them.…”
Section: Literature Reviewsupporting
confidence: 77%
“…For example, in a study on the factors driving the adoption of E-banking services in Zambia based on the UTAUT Model, it was revealed that the UTAUT factors; performance expectancy, effort expectancy, facilitating conditions and behavior intention have a significant impact in the adoption of e-banking services. Social influence was non-significant to the user's intention to adopt e-banking services [12]. Some of the results from these studies are consistent with the original postulations while others contradict them.…”
Section: Literature Reviewsupporting
confidence: 77%
“…The Unified Theory of Acceptance and Use of Technology (UTAUT) was formulated in a quest to harmonise earlier technology adoption models, namely TRA, Theory of Planned Behaviour (TPB), the Technology Acceptance Model (TAM), the Motivational Model, Personal Computer (PC) Utilisation, Diffusion of Innovation (DOI) and the Social Cognitive theories [20]. Venkatesh et al [21] examined eight technology acceptance models and used the findings to identify the four core determinants of intention and usage, and up to four moderators of key relationships.…”
Section: Unified Theory Of Acceptance and Use Of Technologymentioning
confidence: 99%
“…Evolving from the Theory of Reasoned Action (TRA), The Technology Acceptance Model (TAM) was the first in which psychological factors that affect technology acceptance were mentioned. The theory developed and validated better measures through for predicting and explaining technology use [20]. The model suggests that when users are presented with a new technology, a number of factors influence their decision on how they will use the technology [22].…”
Section: Technology Acceptance Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…enhance his or her job performance. Perceived ease of use also influences in a significant way the attitude of an individual through two main mechanisms: self-efficacy and instrumentality[10] [11] [12][13].…”
mentioning
confidence: 99%